2019
DOI: 10.1016/j.amjcard.2018.11.047
|View full text |Cite
|
Sign up to set email alerts
|

A Novel PITX2c Gain-of-Function Mutation, p.Met207Val, in Patients With Familial Atrial Fibrillation

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…These changes could contribute to the long-term stabilization of the arrhythmia by shortening the AP duration (APD) (González de la Fuente et al, 2012). By contrast, whilst the gain-of-function arising from the p.Met207Val mutation has been suggested to increase susceptibility to familial AF (Mechakra et al, 2019), this link remains to be demonstrated directly.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…These changes could contribute to the long-term stabilization of the arrhythmia by shortening the AP duration (APD) (González de la Fuente et al, 2012). By contrast, whilst the gain-of-function arising from the p.Met207Val mutation has been suggested to increase susceptibility to familial AF (Mechakra et al, 2019), this link remains to be demonstrated directly.…”
Section: Introductionmentioning
confidence: 95%
“…Whilst the precise mechanisms underlying AF are complex and poorly understood, AF-induced ionic remodeling and structural cardiac diseases are major factors in initiating and sustaining AF (Grandi et al, 2011; Colman et al, 2013; Koivumäki et al, 2014). However, genome-wide association studies suggested genetic variation contributes to AF susceptibility, with >100 AF-associated loci reported to date (Nielsen et al, 2018), including the atrial-selective transcription factor PITX2 (paired like homeodomain-2) that regulates membrane effector genes associated with AF (Gudbjartsson et al, 2007; Chinchilla et al, 2011; Kirchhof et al, 2011; Qiu et al, 2014; Tao et al, 2014; Lozano-Velasco et al, 2015; Pérez-Hernández et al, 2015; Bai et al, 2018; Mechakra et al, 2019). In these studies, Mechakra et al (2019) identified a non-synonymous mutation c.619A>G (p.Met207Val, rs138163892) of PITX2.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been observed that PITX2 messenger RNA (mRNA) levels are reduced in the atrial cardiomyocytes (CMs) of sustained AF patients carrying risk variants at 4q25 (12). Additionally, PITX2 gain-of-function variants have also been associated with AF in humans, suggesting that expression levels of PITX2 targets must be tightly regulated for cardiac homeostasis (13,14). During vertebrate development, Pitx2 is a key regulator of left-right patterning of the body plan (15)(16)(17).…”
mentioning
confidence: 99%